Exploring backup requirements to complement wind, solar and hydro generation in a highly renewable Spanish power system. (November 2021) - Tapetado, P.; Victoria, M.; Greiner, M.; Usaola, J.
Abstract: A weather-driven model is used to investigate the requirements for the backup generation (annual energy, power capacity and flexibility) in a power system with different penetrations of wind, solar photovoltaics, and hydroelectricity. The impact of interannual variability is assessed by using 26 years of weather data. The flexibility needed for the backup generation is found to be higher as the solar penetration increases since ramps caused by sunrises and sunsets are more significant than those caused by hour-to-hour wind fluctuations. The model is applied to the Spanish power system and two dispatch strategies for reservoir hydro and pumped hydro storage are evaluated. The currently installed gas power capacity is found to be sufficient to secure hourly demand for high renewable penetration. Highlights: Weather-driven model to investigate renewable integration in the Spanish power system. Analysis of the backup generation fleet through an offline flexibility index. Existing backup capacity is sufficient to allow large renewable integration. The required backup flexibility increases for solar-dominant system.